Influence of ecologically relevant urea fertilizer concentrations on nematodes: A microcosm experiment - Rowena B. Caro-Benavides; Ma. Reina Suzette B. Madamba; Nanette Hope N. Sumaya; Ruben F. Amparado, Jr; Joey Genevieve T. Martinez (Spanish Journal of Agricultural Research)
Aim of study: Urea remains one of the most widely used chemical fertilisers in the world and is used extensively in the Philippines as a major source of nitrogen for crops. However, we have a very limited understanding of its impact on soil fauna such as nematodes. In this study, we demonstrated the suitability of the microcosm set-up to assess chemical effects on nematode communities under controlled conditions and determined the effects of urea on nematode communities.